Reorientation of Al-Silm Kaffah Q.S. Al-Baqarah [2] : 208 (Comparative Study of Tafsir Al-Jaila>ni and Tafsir Al-Mishba>h) - Muhammad Alfian Masykur; M. Ikhwanuddin; Eka Prasetiawati (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
The Islam Kafah term which was born from the word al-Silm ka>ffah Qur’an al-Baqarah [2]: 208 has been popular for quite a long time. But, this term is still understood as paradigm that Islamic values must always be implemented as formal legal rules and only focus on symbolic attributes. Such a paradigm of Islam, actually makes it easy for some circles to justify other parties that their Islam is not Kafah or imperfect, and of course this has a negative impact on relations between fellow Muslims. The purpose of this study is to try to reveal the orientation of Sufism and social-society in the word al-Silm ka>ffah as well as to explain its relevance to the contemporary Indonesian context. The method used in this study is a comparative study of exegesis, namely between al-Jaila>ni's interpretation with the s}u>fi> isya>ri feature and al-Mishba>h's interpretation with the al-Ada>bi al-Ijtima>'i feature. The results of this study show that al-Silm ka>ffah implies the necessity for believers to enter Islam as a whole in the sense that it is not only limited to what appears outwardly but must be improved on the inner side which includes the soul, heart and spirit. Al-Silm ka>ffah also means that as a Muslim, he should enter into the essence of Islam, namely peace which is reflected in every behavior or action as a whole, both towards himself, his family, humans in general, even the environment and the universe. By paying attention to the values that have been found, it is hoped that the spirit of implementing Islamic values as a whole can have a more positive output for the Muslims themselves and for society in general.